An evaluation of a prenatal individualised mixed management intervention addressing breastfeeding outcomes and postpartum depression: A ramdomised controlled trial. Issue 9 (15th February 2021) - Zhao, Ying; Lin, Qiping; Wang, Jing
Abstract: Aims and objectives: To determine the effects of an individualised mixed management combined lactation education and psychoeducation intervention on breastfeeding outcomes and postpartum depression (PPD) at 3 and 42 days postpartum. Background: Pregnant women with antenatal depression are prone to postpartum depression and failure in breastfeeding. Design: Eligible women participated in a randomised single‐blind controlled trial. Results are reported as per the CONSORT 2010 statement. Methods: Participants were recruited from December 2017–August 2018 at a major teaching hospital located in Shanghai. Primiparous women ( n = 182) with an Edinburgh Postnatal Depression Scale score ≥9 were randomly enrolled in the intervention group ( n = 91) or the control group ( n = 91). The intervention group participated in a 4‐session face‐to‐face mixed management intervention targeting perinatal depression and breastfeeding. The control group received usual care. Breastfeeding and psychological outcomes were measured during the third trimester (≥28 weeks and <35 weeks), and at 3 and 42 days postpartum. Results: There were statistically significant differences in rates of overall and exclusive breastfeeding, initial breastfeeding experience, breastfeeding behaviour and self‐efficacy between the two groups at 3 and 42 days postpartum ( p < .05). Intention‐to‐treat linear mixed model analysis showed that EPDS scores were statistically significantly different between groups over time ( F = 20.42, p < .001). Intervention group were more satisfied with their husbands' care and care received during the first month postpartum ( p < .05). Conclusions: The results demonstrate the effectiveness and feasibility of delivering an individualised mixed management intervention combining lactation guidance with psychological support during pregnancy. Relevance to clinical practice: This study supports the need to identify pregnant women at risk of perinatal depression and indicates that the prenatal individualised mixed management intervention has the potential to reduce PPD and help achieve better breastfeeding outcomes.